Focal Hyperhidrosis Associated with Recurrent Urinary Tract Infections - Dina Ismail; Vidya Madhwapathi; Evmorfia Ladoyanni (Case Reports in Dermatological Medicine)
Hyperhidrosis affects almost 3% of the population and is characterized by sweating that occurs in excess of that needed for normal thermoregulation. It can occur as a primary disease or secondary to underlying clinical conditions. Hyperhidrosis can stem from neurogenic sympathetic over activity involving normal eccrine glands. We report the interesting case of a 75-year-old male patient with a 6-month history of new onset secondary focal hyperhidrosis of buttocks, pelvis, and upper thighs. Each time his symptoms worsened he was found to have culture positive urine samples for Escherichia coli (E. coli). He underwent urological investigation and was found to have urethral strictures and cystitis. The hyperhidrosis improved each time his urinary tract infection (UTI) was treated with antibiotics and continued to remain stable with a course of prophylactic trimethoprim. We hypothesize that the patient’s urethral strictures led to inhibition in voiding which in turn increased the susceptibility to UTIs. Accumulation of urine and increased bladder pressure in turn raised sympathetic nerve discharge leading to excessive sweating. We recommend that a urine dip form part of the routine assessment of patients presenting with new onset focal hyperhidrosis of pelvis, buttocks, and upper thighs. Timely urological referral should be made for all male patients with recurrent UTI. To the authors’ knowledge, there have been no other reports of UTI-associated focal hyperhidrosis.